OTOMATISASI JEMURAN PAKAIAN MENGGUNAKAN SENSOR HUJAN BERBASIS ARDUINO VIA BOT WHATSAPP - Andy; Handoko, Koko (LPPM Universitas Putera Batam, 2025)
Indonesia has two seasons, namely the dry season and the rainy season. During the dry season, the need for sunlight is very much needed, one example is drying wet clothes. However, when the weather is uncertain, the job of drying clothes becomes quite troublesome and will take time and energy to lift and dry the clothes again. In this study, researchers will design a prototype that can protect clotheslines when it rains and provide notifications to the user's WhatsApp that this prototype detects rain and immediately protects the clotheslines from the rain. This prototype is designed using Arduino Uno as the main controller on this prototype and can be connected to the internet network, a rain sensor as a rain detector, and a micro servo as a roof driver above the clothesline. The results of conducting trials on the prototype are that this prototype can protect clotheslines from rain and also successfully send notifications in the form of WhatsApp messages that rain has been detected.